Anti B cell targeted immunotherapy for treatment of refractory autoimmune haemolytic anaemia in a young infant. Issue 4 (1st April 2003) - Ng, P C; Lee, K K M; Lo, A F C; Li, C K; Fok, T F
Abstract : We report the case of an 8 week old infant with fulminant autoimmune haemolytic anaemia refractory to conventional immunomodulating treatment. Massive haemolysis resulted in cardiac decompensation and acute renal failure which necessitated mechanical ventilation and peritoneal dialysis. Rituximab, a chimeric anti-CD20 monoclonal antibody, halted progression of the haemolytic process, but the patient died of acute viral pneumonia and disseminated fungal infection. Earlier introduction of rituximab might have prevented the renal complications. Paediatricians should be aware of this useful therapeutic tool for treatment of refractory autoimmune haemolytic anaemia and balance its use against the risk of potential life threatening infection.